2022
DOI: 10.1097/dbp.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Criando Niños Con Cariño: Primary Care-Based Group Parenting Program Adaptation and Pilot

Abstract: :Objective:This study culturally adapted and piloted a primary care-based group parenting program (Child-Adult Relationship Enhancement in Primary Care, PriCARE) for Spanish-speaking, Hispanic parents of 2- to 6-year-old children.Methods:The process was informed by the cultural adaptation literature, expert consultation, and focus group data from 18 previous PriCARE, eligible Cariño, and initial Cariño test participants. As adaptations were made, an implementation framework was applied to systematically record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…PriCARE/CARIÑO was developed with input from and evaluated in underserved families. The existing evidence base favoring its efficacy is strong [38][39][40][41]. Three RCTs and one pre/post pilot have demonstrated improvements in key proximal outcomes, including child behavior problems, harsh parenting, and parent stress scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PriCARE/CARIÑO was developed with input from and evaluated in underserved families. The existing evidence base favoring its efficacy is strong [38][39][40][41]. Three RCTs and one pre/post pilot have demonstrated improvements in key proximal outcomes, including child behavior problems, harsh parenting, and parent stress scores.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomized controlled trials demonstrate that PriCARE/CARIÑO decreases child behavior problems, harsh and permissive parenting, and parent stress, but we have not previously examined the occurrence of CM or CM risk scores as outcomes [38][39][40][41]. Furthermore, though we have addressed multiple implementation challenges [42], we have yet to rigorously assess implementation determinants (barriers/facilitators) related to referrals, enrollment, and attendance that can inform the development of strategies for implementing and scalingup PriCARE/CARIÑO.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…token economy [95]). In general, available research has found that culturally adapted and standard ESTs have similar effects [96] and many comprehensively adapted interventions are at the acceptability-testing stage [95,97].…”
Section: Increasing Cultural Relevancementioning
confidence: 99%
“…PriCARE is an evidence-based intervention that has demonstrated decreases in child behavior problems, harsh and permissive parenting, and parent stress ( Gurwitch et al, 2016 ; Schilling et al, 2017 , 2020 ; Wood et al, 2021 ). Criando Niños con Cariño (Raising Children with Care) is a cultural adaptation of PriCARE for Spanish-speaking, Hispanic parents ( Schilling et al, under review ). PriCARE/ Cariño is a manualized skill-based program delivered in the primary care setting by two licensed clinical social workers (LCSWs) during 6 weekly 90-minute sessions to groups of 6–10 parents.…”
Section: Child–adult Relationship Enhancement In Primary Carementioning
confidence: 99%